2013
DOI: 10.6007/ijarbss/v3-i7/27
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Design, Validity and Reliability in General Social Survey

Abstract: Following the proliferation of the research in the study of social network, the debate on the design and use of General Social Survey has dominated research articles addressing social network question. For example the three prominent authors have propelled a discussion on various anomalies of the findings from different articles on social change which as result raise a question on reliability and validity. Although in all the articles the design on sampling and measurement instrument are featured, the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Of the 20 studies, only two were rated as having a low risk of bias (≥67% of total score) with an average of 0.73 of the total score; 10 were rated as having a moderate risk of bias (>33 and <67% of the total score) with an average of 0.45 of the total score and 8 studies were rated as having a high risk of bias (<33% of total score) with an average of 0.32 of the total score. Only 6 studies (33%) reported power calculations to determine a sufficient sample size and only 3 studies met the assumption of randomization, which is not so important to determine the reliability and validity of questionnaires [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 20 studies, only two were rated as having a low risk of bias (≥67% of total score) with an average of 0.73 of the total score; 10 were rated as having a moderate risk of bias (>33 and <67% of the total score) with an average of 0.45 of the total score and 8 studies were rated as having a high risk of bias (<33% of total score) with an average of 0.32 of the total score. Only 6 studies (33%) reported power calculations to determine a sufficient sample size and only 3 studies met the assumption of randomization, which is not so important to determine the reliability and validity of questionnaires [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 19 studies, only two were rated as having a low risk of bias (> 67% of total score) with average of 0.73 of total score; 9 were rated as having moderate risk of bias (> 33 and < 67% of the total score) with average of 0.45 of total score and 8 studies were rated as having a high risk of bias (<33% of total score) with average of 0.32 of total score. Only 6 studies (33 %) reported power calculations to determine sufficient sample size and only 3 studies met the assumption of randomization, which is actually not so important to determine reliability and validity of questionnaires [74]. [37] EHIS * + -0 0 1 1 0 1 0 1…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this study uses a formal power analysis to determine the minimum sample size required for generalizability (Lameck 2013). A key component of the power analysis is the size effect, which is an estimate due to the lack of prior research work in this area of study (Jones et al 2003).…”
Section: Power Analysismentioning
confidence: 99%